KUALITAS PENGAWASAN PIMPINAN DALAM PEMBINAAN DISIPLIN ANGGOTA SATUAN POLISI PAMONG PRAJA PROVINSI LAMPUNG - Malik Malik (Universitas Bandar Lampung (UBL), 2018)
ABSTRACT Leadership Quality Supervision in the Discipline Development of Members of the Lampung Provincial Civil Service Police Unit. The problems in this study are: (1) How is the quality of leadership supervision in the Civil Service Police Unit in Lampung Province. (2) How to guide member discipline in the Civil Service Police Unit in Lampung Province. The research method used qualitatively with descriptive analysis method, the use of this method is to describe and study qualitatively, supervising the leadership in fostering discipline of members of the Civil Service Police Unit of Lampung Province, reviewing qualitatively, how all data is obtained directly from informants in the field by using interviews and Study documents. Quality Supervision of leaders in the Civil Service Police Unit in Lampung Province, in general has shown compliance with Governor Regulation No. 6 of 2016 concerning the main duties and functions of the Lampung Provincial Civil Service Police Unit, then the leadership in carrying out direct supervision, namely by directly monitoring the activities being carried out by employees, while indirect supervision by the leadership is by monitoring employees through monthly reports and absent from routine employee activities carried out. The implementation of discipline in the Civil Service Police Unit in Lampung Province, especially the adherence to time has been relatively good, but there are still those who often take advantage of the time to carry out personal tasks if given an external assignment, then there are still frequent tasks given by the leadership, so employees sometimes unable to set the time to complete the work being carried out as a mandatory task.